Betti base derived P-stereogenic phosphine-diamidophosphite ligands with a single atom spacer and their application in asymmetric catalysis. Issue 5 (8th December 2021) - Chakrabortty, Soumyadeep; Konieczny, Katharina; Müller, Bernd H.; Spannenberg, Anke; Kamer, Paul C. J.; de Vries, Johannes G.
Abstract : Small bite-angle P -chirogenic PNP ligands have been synthesized stereo-selectively and employed in Rh-catalyzed asymmetric hydrogenation and Pd-catalyzed asymmetric allylic substitution resulting in moderate to excellent enantioselectivities. Abstract : A set of hybrid P -stereogenic phosphine-diamidophosphite ligands based on the Betti base backbone has been synthesized. The ligands possess five chiral centers including the P -chirality in both the phosphorus atoms. The synthesis involves the incorporation of a P -chiral P–N synthon with a stereochemically defined P -chiral diamidophosphite as a coupling partner. The new ligands were applied in Rh-catalyzed asymmetric hydrogenation of several dehydroamino acids and in the Pd-catalzyed asymmetric allylic substitution of diphenyl allyl acetate. Moderate ee s upto 74% in allylic substitution and excellent ee s up to 99% were obtained in asymmetric hydrogenation using this new set of hybdrid PNP ligands.